“Lung-on-a-chip” as an instrument for studying the pathophysiology of human respiration - Oksana A. Zhukova; Iuliia V. Ozerskaya; Dmitry V. Basmanov; Vsevolod Yu. Stolyarov; Vladimir G. Bogush; Vladimir V. Kolesov; Kirill A. Zykov; Gaukhar M. Yusubalieva; Vladimir P. Baklaushev (Клиническая практика)
“Lung-on-a-chip” (LoC) is a microfluidic device, imitating the gas-fluid interface of the pulmonary alveole in the human lung and intended for pathophysiological, pharmacological and molecular-biological studies of the air-blood barrier in vitro. The LoC device itself contains a system of fluid and gas microchannels, separated with a semipermeable elastic membrane, containing a polymer base and the alveolar cell elements. Depending on the type of LoC (single-, double- and three-channel), the membrane may contain only alveolocytes or alveolocytes combined with other cells — endotheliocytes, fibroblasts, alveolar macrophages or tumor cells. Some LoC models also include proteinic or hydrogel stroma, imitating the pulmonary interstitium. The first double-channel LoC variant, in which one side of the membrane contained an alveolocytic monolayer and the other side — a monolayer of endotheliocytes, was developed in 2010 by a group of scientists from the Harvard University for maximally precise in vitro reproduction of the micro-environment and biomechanics operations of the alveoli. Modern LoC modifications include the same elements and differ only by the construction of the microfluidic system, by the biomaterial of semipermeable membrane, by the composition of cellular and stromal elements and by specific tasks to be solved. Besides the LoC imitating the hematoalveolar barrier, there are modifications for studying the specific pathophysiological processes, for the screening of medicinal products, for modeling specific diseases, for example, lung cancer, chronic obstructive pulmonary disease or asthma. In the present review, we have analyzed the existing types of LoC, the biomaterials used, the methods of detecting molecular processes within the microfluidic devices and the main directions of research to be conducted using the “lung-on-a-chip”.